Isolation, biochemical characterization, and greenhouse authentication of chickpea (Cicer arietinum L.) rhizobia collected from some major chickpea growing areas of Woldia, North Wollo, Ethiopia - Kelemu Yimenu Gebre; Abebe Girma Demissie; Aderajew Adgo Tesema; Habtamu Zegeye Belay; Mekashaw Worku Akalye; Agere Bereket Friew; Fisseha Getachew Baye; Habtie Bassie Felatie; Mezgebu Abunie Yohannes; Marye Alemu Eshetu; Wondye Ayalew Shiferaw (PLoS ONE, 2025)
Chickpea ( Cicer arietinum L. ) is a vital legume crop worldwide, valued for its high nutritional content and significant contribution to food security and soil fertility through biological nitrogen fixation. Despite its importance, chickpea yields remain suboptimal in many regions, including Ethiopia, primarily due to constraints such as poor soil fertility and inadequate use of effective rhizobia inoculants. This study aimed to isolate and characterize native Rhizobium strains from chickpea root nodules collected from fields in the Woldia region and to assess their potential to promote plant growth. A total of 41 bacterial isolates were obtained, of which 12 were presumptively identified as Rhizobium based on growth characteristics on Congo red and bromothymol blue media. These isolates were further characterized morphologically and biochemically. Five biochemically promising isolates were selected for evaluation in a controlled 45-day greenhouse experiment under sterile conditions. Inoculation with these isolates significantly enhanced seed germination and early seedling growth compared to uninoculated controls. The symbiotic effectiveness of the isolates ranged from 74.3% to 121.9%, with isolates WUSFDG-23, WUSFMC-31, and WUSFMC-23 demonstrating high effectiveness, isolate WUSFDG-23 markedly increased nodulation and biomass accumulation. This study highlights the potential of native Rhizobium isolates from Woldia chickpea fields, especially WUSFDG-23, as effective bio-inoculants to promote sustainable chickpea production and reduce dependence on chemical fertilizers.